An exploratory factor analysis of holistic thinking behaviour of the teachers in teaching higher-order thinking skills - Hashim, Huda Afiqah (NUN Gemilang Enterprise, 2023)
Higher-order thinking skills (HOTS) are critical skills that a student needs to master, especially in the era of 21st Century Learning. Teacher plays a vital role in inculcating and instilling the values of HOTS in the classroom. Such as more than HOTS, knowledge is required to implement HOTS teaching because the teacher’s thinking is the main factor in successfully fulfilling the education agenda in Malaysia. Therefore, this paper aims to develop an instrument of holistic thinking behaviour among teachers in secondary schools. The study used a quantitative research design to know the facts and figures of the construct's reliability and validity. A questionnaire was developed with 24 measurement items comprising six main components: metacognition, creative thinking, flexible thinking, interdependent thinking, efficacy in thinking and precision language of thinking. This instrument has gone through the process of face validity and content validity by three academic experts. A pilot study was conducted involving 108 respondents in the state of Terengganu. Data were analysed using the Statistical Package for Social Sciences (SPSS) version 25 via exploratory factor analysis (EFA), Bartlett's sphericity test, Kaiser-Meyer-Olkin (KMO) sampling adequacy test and Cronbach’s Alpha reliability test. The study's findings have shown that the model produces five components with 23 items. Bartlett’s test of sphericity for all components gave a significant value (P<0.05), significant sampling adequacy (KMO>0.6) and a Cronbach’s Alpha value that exceeded the threshold value of 0.7. Overall, the results of the EFA analysis show that the instrument has high validity and reliability for measuring the construct of holistic thinking behaviour construct. This study gives implications from the aspect of holistic thinking among teachers, which includes five main elements that act as catalysts in teaching and instil higher-order thinking skills among students in the classroom.